Inhibition of the renin-angiotensin system in patients with upper gastrointestinal adenocarcinoma - Wirsik, Naita Maren; Stengel, Svenja; Jung, Jin-On; Peters, Leila; Crnovrsanin, Nerma; Nienhüser, Henrik; Schleußner, Nikolai; Hamm, Alexander; Büchler, Markus W.; Schmidt, Thomas (The British journal of surgery, 2024)
Neoadjuvant chemotherapy or radiochemotherapy combined with surgical resection represents the standard treatment for advanced oesophagogastric adenocarcinoma (OGA)1. No superiority of either treatment, however, has been shown2. Not only the cancer itself, but also the tumour microenvironment (TME) consisting of multiple cell types including fibroblasts, may influence the response to neoadjuvant treatment3.Renin-angiotensin aldosterone system inhibitors (RAAS-I) have been shown to modulate fibroblasts as part of the TME and improve overall survival (OS) in combination with antiangiogenic treatment in metastatic colorectal cancer4. This effect is due to a reduction in tumour stiffness and vascular normalization. This leads to the hypothesis that neoadjuvant treatment with chemotherapy could be more effective in patients treated with RAAS-I. Therefore, the aim of this study was to investigate the influence of RAAS-I on outcomes in patients with OGA undergoing multimodal treatment. These patients had neoadjuvant chemotherapy as standard treatment.